Genomic and phenotypic biology of a novel Dickeya zeae WH1 isolated from rice in China: Insights into pathogenicity and virulence factors - Tan, Xiao-Juan; Zhang, Zhi-Wei; Xiao, Jing-Jing; Wang, Wei; He, Feng; Gao, Xuan; Jiang, Bin; Shen, Liang; Wang, Xu; Sun, Yang; Zhu, Guo-Ping (Frontiers in Microbiology, 2022)
Soft rot caused by Dickeya zeae is an important bacterial disease of rice and other plants worldwide. In this study, Nanopore and Illumina sequencing platforms were used to sequence high-quality complete genome of a novel D. zeae strain WH1 (size: 4.68 Mb; depth: 322.37x for Nanopore, 243.51x for Illumina; GC content: 53.59%), which was isolated from healthy rice root surface together with Paenibacillus polymyxa, a potential biocontrol bacterium against D. zeae strain WH1. However, the pure WH1 culture presented severe pathogenicity. Multilocus sequence analysis (MLSA) indicated that strains WH1, EC1 and EC2 isolated from rice were grouped into a clade differentiated from other D. zeae strains. The average nucleotide identity (ANI) and DNA-DNA hybridization (DDH) analyses demonstrated that WH1 was phylogenetically closest to EC2. Furthermore, the pathogenicity determinants and virulence factors of WH1 were mainly analyzed through genomic comparison with complete genomes of other D. zeae strains with high virulence (EC1, EC2, MS1 and MS2). The results revealed that plant cell wall-degrading extracellular enzymes (PCWDEs), flagellar and chemotaxis, and quorum sensing were highly conserved in all analyzed genomes, which were confirmed through phenotypic assays. Besides, WH1 harbored type I, II, III, and VI secretion systems (T1SS, T2SS, T3SS, and T6SS), but lost T4SS and T5SS. Like strains MS1 and MS2 isolated from banana, WH1 harbored genes encoding both capsule polysaccharide (CPS) and exopolysaccharide (EPS) biosynthesis. The results of pathogenicity assays demonstrated that WH1 produced severe soft rot symptoms on potato tubers, carrot, radish and Chinese cabbage. Meanwhile, WH1 also produced phytotoxin(s) to inhibit rice seeds germination with 87% of inhibitory rate at laboratory conditions. More importantly, we confirmed that phytotoxin(s) produced by WH1 is different from zeamines produced by EC1. Comparative genomics analyses and phenotypic and pathogenicity assays suggested that WH1 likely evolved through a pathway different from the other D. zeae strains from rice, producing a new type of rice foot rot pathogen. These findings highlight the emergence of a new type of D. zeae strain with high virulence causing rice and other plants soft rot.